2020
DOI: 10.1002/jbt.22521
|View full text |Cite
|
Sign up to set email alerts
|

Combined approaches for evaluation of xenoestrogen neural toxicity and thyroid dysfunction: Screening of oxido‐nitrosative markers, DNA fragmentation, and biogenic amine degradation

Abstract: Anthropogenic chemicals such as parabens and triclosan are used in personal care products. Due to their ability to decrease or prevent bacterial contamination and act as preservatives, these chemicals are used in cosmetic manufacturing processes to increase the shelf life of products. In this study, we assessed the side effects of environmental estrogens (such as the xenoestrogen butylparaben and the antimicrobial agent and preservative triclosan) on thyroid function, brain monoamine levels, and DNA aberration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…For instance, administration of TCS in concentration up to 0.345 mmol/kg/day resulted in a decrease of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in female mice (Cao et al 2018), while at the higher oral dose (0.639 mmol/ kg/day), increased both FSH and LH were measured in Sprague Dawley rats (Abd-Elhakim et al 2018). However, a comparable reduction in thyroid hormones, T3 and T4, was observed in male Wistar albino rats (Taha et al 2020), female Sprague Dawley rats (Abd-Elhakim et al 2018) and female mice (Cao et al 2018). The findings are in agreement with the in vitro data suggesting TCS hypothyroidism-inducing effects (Butt et al 2011).…”
Section: In Vivo Analysesmentioning
confidence: 63%
“…For instance, administration of TCS in concentration up to 0.345 mmol/kg/day resulted in a decrease of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in female mice (Cao et al 2018), while at the higher oral dose (0.639 mmol/ kg/day), increased both FSH and LH were measured in Sprague Dawley rats (Abd-Elhakim et al 2018). However, a comparable reduction in thyroid hormones, T3 and T4, was observed in male Wistar albino rats (Taha et al 2020), female Sprague Dawley rats (Abd-Elhakim et al 2018) and female mice (Cao et al 2018). The findings are in agreement with the in vitro data suggesting TCS hypothyroidism-inducing effects (Butt et al 2011).…”
Section: In Vivo Analysesmentioning
confidence: 63%
“…Exposure to BuP increases thyroid peroxidase activity, serum TSH levels, and decreases T4 levels and type 1 iodothyronine deiodinase (D1) activity in rats 25 . When exposed to a higher dose (50 mg/kg bw/day) of BuP for a longer period of time (60 days), rats develop significant hypothyroidism 26 . In vivo concentrations of PBs are associated with abnormal thyroid hormone levels and may also affect the health of offspring through the mother 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the BuP exposure group, rats were injected subcutaneously in the neck at a dose of 50 mg/kg body weight/day for 4 weeks. The concentration and duration of treatment were selected based on previous studies 21 , 25 , 26 . For mice, the LD50 (subcutaneous) of BuP is > 2500 mg/kg (11.56 mmol/kg).…”
Section: Methodsmentioning
confidence: 99%
“…The results from epidemiological studies of TCS and thyroid function in humans are not consistent [ 129 , 130 ]. A recent study on young male Wistar albino rats showed that a high dose of TCS led to symptoms of hypothyroidism that were expressed by significant changes in FT3, FT4, and TSH (triiodothyronine, thyroxine, and thyroid-stimulating hormone, respectively) levels [ 131 ]. The same reduction of FT3 and FT4 was observed in Sprague-Dawley rats [ 132 ] and female mice [ 133 ].…”
Section: Toxicity Studies On Tcsmentioning
confidence: 99%